Measurement of plasma density formed at passing of a sequeence of relativistic electron bunches through the neutral gas - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I.; Ivanov, B.I.; Prishchepov, V.P. (Вопросы атомной науки и техники, 2013)
Using an open barrel-shaped resonator (OBR) plasma density, produced by a sequence of duration 2 μs of relativistic electron bunches, each of energy 4.5 MeV and charge 0.16 nC, in air at pressure of 10…60 Torr was measured. The plasma density was determined from the shift of the OBR resonant frequency estimated after measuring the reduction of oscillations amplitude in plasma loaded OBR at the initial frequency of OBR. It was shown that the maximum density of the produced plasma reaches 3·10¹⁰ cm⁻³ at wakefield excitation in a semi-infinite plasma waveguide and 10¹¹ – in plasma resonator